Медиа білім беру үрдісінде студенттердің сыни ойлауын жетілдіру критерийлері мен көрсеткіштері - Ташетов, А.А. (My University, 2016)
In this article, what be going on today in informative society of intensive changes and additions in development of strategic plan of development of home education with the purpose of included in outer educational space, requires passing to the new model of the national system educations taking into account general world tendencies. To that end in educational process perfection is envisaged criteria and indexes of the critical thinking of personality.
Keywords: Informative society; education in INSTITUTIONS of higher learning; space of world education; medias of information; critical thinking